(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Polymicrogyria (PMG) is a malformation of cortical development (MCD) and is classified as an ICD secondary to abnormal post-migration neuronal development [[1], [2], [3], [4]]. In addition to the spectrum of neurological diseases, 65–87% of patients with PMG develop epilepsy, and most experience seizures within the first five years of life [1]. Approximately 65% of patients with PMG-associated epilepsy have drug-resistant epilepsy (DRE). Epilepsy surgery should be considered in these patients with DRE associated with PMG [1,5,6]. Although epilepsy surgery has been shown to be superior to continuous anticonvulsant medication alone for seizure control in a subset of appropriately selected patients with EMH-associated ED [[7], [8], [9]], only 5% of all MCI-associated epilepsy surgeries target EMH-associated epilepsy [10]. The complexity of surgery in these patients reflects the presence of extensive (sometimes bilateral) brain malformations in many cases, and the fact that the EMH cortex typically maintains normal brain function [[1], [11]]. Given these concerns, healthcare providers may choose not to perform surgery in this particular group of patients with EMH, and thus surgery is underutilized or delayed [10]